Male voices stories of boys learning through making music - Harrison, Scott D. 1962- (ACER Press, 2009)
Male Voices describes a diverse group of Australian boys and men actively engaging in making music. The book discusses how these males may need to overcome societal resistance and stereotypical images to pursue music but, when they achieve this, music makes a powerful, joyful difference to their lives.